Protection Against Cold Storage–Induced Renal Tubular Cell Apoptosis. Issue 11 (November 2015) - Jain, Swati; Keys, Daniel; Ljubanovic, Danica; Edelstein, Charles L.; Jani, Alkesh
Abstract : Background: Prolonged cold storage (CS) of donor kidneys is associated with tubular cell apoptosis and caspase-3 activation. We have previously shown that pancaspase inhibition prevents CS-associated tubular apoptosis. Because of the nonspecific nature of pancaspase inhibitors, which block all caspases including proinflammatory caspase-1, the effect of specific caspase-3 inhibition during CS is unknown. X-linked inhibitor of apoptosis (XIAP) is the most potent naturally occurring specific inhibitor of caspase-3. We hypothesized that prolonged CS would decrease XIAP, whereas upregulation of XIAP with the novel compound UCF-101 would protect against caspase-3 activation and tubular cell apoptosis. Methods: LLC-PK1 tubular cells and whole kidneys from C57BL/6 mice were subjected to prolonged CS with or without UCF-101, and examined for XIAP, caspase-3, and tubular apoptosis. Results: Tubular cells subjected to prolonged CS in vitro demonstrated significantly decreased XIAP and significantly increased apoptosis, caspase-3 protein and activity. UCF-101 treatment significantly increased XIAP, significantly decreased capsase-3 protein and activity, and protected against apoptosis. To determine the therapeutic significance, whole kidneys were subjected to prolonged CS with UCF-101. UCF-101 significantly increased XIAP in donor kidneys and protected against apoptosis. Conclusions: Prolonged CS of tubular cells in vitro and whole mouse kidneys ex vivo is associated with loss of XIAP and subsequent tubular cell apoptosis. UCF-101 protects against the loss of XIAP during prolonged CS both in vitro and ex vivo, and is associated with significantly reduced tubular cell apoptosis. UCF-101 may represent an attractive approach to improve organ preservation. Abstract : Jani et al demonstrate the contributions of the inhibitor of caspase-3 X-linked inhibitor of apoptosis (XIAP) in tubular cell apoptosis and demonstrate that the compound UCF-101 protects against loss of XIAP during prolonged cold storage, in vitro and ex vivo.